ANTI-INFLAMMATORY PREDICTION OF PERONEMIN COMPOUNDS FROM SUNGKAI (Peronema canescens Jack) AND THEIR DERIVATIVES - Sofia Nurjannah; Dewi Arum; Indra Lasmana Tarigan; Madyawati Latief (UPT Publication and Journal Management, Islamic University of Kalimantan, 2023)
Seven Sungkai Peronemins compounds belong to the alkaloid group, Peronemin A2, A3, B1, B2, B3, C1, and D1. Sungkai contains several bioactive compounds, triterpenoids, alkaloids, flavonoids, phenolics, steroids, and saponins which can act as anti-inflammatory candidates. Geometry optimization to find the most stable molecular structure and SMILES of the peronemin compound was used to predict pIC50 using the pChEMBL® program. From the test results of seven peronemin compounds, several candidate target molecules were obtained as potential anti-inflammatory agents, namely Angiotensin II type 2 (AT-2) receptors, Dihydrofolate reductase, and Phosphodiesterase 7A. Of the three target molecules, the Angiotensin II type 2 (AT-2) receptor on peronemin C1 has the highest pIC50 value of 6.79. The highest pIC50 value indicates an exponentially potent inhibitor in determining its biological activity. The anti-inflammatory function of AT-2 is revealed by its involvement in modulating mediators such as cytokines and chemokines.